“Ecclesiastical Authority Terror”. The Downgrading of the Szigetszentmiklós Reformed Parish to Mission Parish in 1956 - LÁNYI, Gábor (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2020)
On 24 May 1956, Délpest Reformed Diocese – by the consent of the Danubian Reformed Church District– downgraded the Szigetszentmiklós Reformed Parish to the status of mission parish. The 700 members strong, almost 400 hundred years old parish’s chief elder was also relieved of his duties whilst the consistory was dissolved. The downgrading of the long-standing parish, the dis-solution of the elected consistory, and the deprivation of its right to elect its minister gave rise to protests both inside and outside the parish. An array of scandals, disciplinary issues, and difficult as well as intricate lawsuits followed. The matter also generated waves in the entire Reformed Church since the presidium of the diocese overlooked the ecclesiastic rules and regulations, ordering the downgrade without the consent of the diocesan assembly –also assisted by the presidium of the church district–, accepting the new situation and appointing the mission minister. The case of Szigetszentmiklós is a great example to understand the global picture of the actions taken against the disloyal ministers and consistories by the ecclesiastic governance intertwined with the one-party state.